EFFORT INCREASES LEARNING RESULTS STUDENT CLASS VII B SMP NEGERI 7 CIMAHI SUBSEQUENT DIFFERENCE THROUGH COOPERATIVE LEARNING MODEL TYPE STAD - Abu Muchlis; Agung Maulana; Hoer Mutaqin; R Bambang Aryan Soekisno (Journal Of Educational Experts (JEE), 2018)
This Research Entitled: Efforts to Improve Student Results Class VII B SMP Negeri 7 Cimahi In The Main Stage Through the Cooperative Learning Model Type STAD.  This study reveals the problem: Is Learning in the Main Stage Through Cooperative Learning Model Type STAD can improve Student Learning Outcomes? In accordance with the problems mentioned above, the purpose of this study is to determine the effectiveness of learning in the subject of the set through cooperative learning model type STAD can improve student learning outcomes.This research was conducted on the students of class VII B SMP Negeri 7 Cimahi with 35 students, consisting of 17 male students and 18 female students. This study was conducted in two cycles with the results of data processing showed that the material "Himpunan" students experience improvement in achievement after using STAD type cooperative learning model that is in the first cycle students' learning mastery reaches 25.71% with an average value of 63.71; on the second cycle of student learning completeness reached 88.57% with an average value of 77.29.Based on the result of research, it is known that Through Model Learning Cooperative Type STAD can improve student learning outcomes. Therefore this learning model should be applicable by the teacher when the teaching and learning process takes place as an alternative model of learning on certain topics.